2015
DOI: 10.1016/j.jbusres.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing alcohol harm: A systematic social marketing review (2000–2014)

Abstract: HighlightsThis study provides a review of evidence behind social marketing effectiveness in the area of problem behaviours associated with alcohol drinking. This paper presents a review of interventions and their evaluations published in peer-reviewed journals between 2000-2014 to identify the role and use of the key elements of social marketing interventions aiming to minimize harm from alcohol consumption. Social marketing interventions reviewed in this study were found to be largely effective in creating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
143
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 44 publications
9
143
2
1
Order By: Relevance
“…Alcohol-related interventions that employ social marketing principles are shown to achieve good results in tackling alcohol-related harm: they have been found to create some immediate but also longer-term changes via attitude, behavioral intention, and/or raising awareness; some also achieved positive behavioral outcomes (Stead et al, 2007;Kubacki et al, 2015). The majority of evaluated alcohol-related social marketing interventions published to date were oriented downstream (the target population was primarily young people and the problem addressed was either alcohol consumption or drink driving); only a few interventions were oriented midstream (e.g., targeting medical and health professionals) (Stead et al, 2007;Kubacki et al, 2015).…”
Section: A Midstream Social Marketing Approach To Increase Retailers'mentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohol-related interventions that employ social marketing principles are shown to achieve good results in tackling alcohol-related harm: they have been found to create some immediate but also longer-term changes via attitude, behavioral intention, and/or raising awareness; some also achieved positive behavioral outcomes (Stead et al, 2007;Kubacki et al, 2015). The majority of evaluated alcohol-related social marketing interventions published to date were oriented downstream (the target population was primarily young people and the problem addressed was either alcohol consumption or drink driving); only a few interventions were oriented midstream (e.g., targeting medical and health professionals) (Stead et al, 2007;Kubacki et al, 2015).…”
Section: A Midstream Social Marketing Approach To Increase Retailers'mentioning
confidence: 99%
“…The majority of evaluated alcohol-related social marketing interventions published to date were oriented downstream (the target population was primarily young people and the problem addressed was either alcohol consumption or drink driving); only a few interventions were oriented midstream (e.g., targeting medical and health professionals) (Stead et al, 2007;Kubacki et al, 2015). However, to solve such stubborn problems as alcohol-related problems, we need to employ additional strategies and approaches; focusing on young people is insufficient.…”
Section: A Midstream Social Marketing Approach To Increase Retailers'mentioning
confidence: 99%
See 1 more Smart Citation
“…A 2007 review noted several studies showed significant short-term effects and two showed some effect over two years [15]. A more recent review of 23 social marketing interventions targeting alcohol related harm reported that 13 of the 16 that reported on behavioral outcomes identified at least one positive outcome [16]. In both reviews, the successful interventions tended to be those that incorporated all or most of the elements of social marketing rather than uni-dimensional ‘education’ or ‘communication’ campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…First, social marketing is recognized to be an effective way of changing people's behavior in order to improve their personal welfare and that of society (Andreasen, 1994;Dibb and Carrigan, 2013). Thus, social marketing campaigns have been widely used to reduce adverse behavior in young people in public health areas such as smoking, alcohol and drug consumption (for a systematic review see Kubacki et al, 2015). Second, social marketing is also interested in analyzing the possible negative outcomes of marketing activities on individual or social behavior (Hastings and Saren, 2003).…”
Section: Introductionmentioning
confidence: 99%